Is the combination of propranolol and flunarizine better than propranolol, flunarizine and amitriptyline alone in prophylaxis of migraine? An observational study at a tertiary care centre of North India - Dixit, Madhumita; Singh, Abhishek K.; Nim, Dwividendra K.; Chaurasia, Rakesh C. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Migraine is a primary headache disorder marked by recurrent attacks of pain and associated symptoms. Propranolol is traditionally considered highly effective for migraine prophylaxis, but other drugs have recently shown promise. Methods: This study was a prospective, observational, randomized, parallel-arm, unicentric trial conducted in the neurology department of a tertiary care hospital in North India. Patients with migraine without aura were randomly assigned to one of four treatment groups. After obtaining consent, patients were randomized using a random number table. Group 1 received propranolol (80 mg), group 2 received flunarizine (10 mg), group 3 received a combination of propranolol (40 mg) and flunarizine (10 mg), and group 4 received amitriptyline (10 mg) daily. The primary outcome was a change in the frequency of migraine days, while secondary outcomes included changes in moderate-to-severe headache days and disability levels. Results: The combination of propranolol (40 mg) and flunarizine (10 mg) was significantly more effective in reducing the frequency of migraine attacks at the end of 3 months compared to the group receiving amitriptyline (10 mg). However, no significant differences between the groups were observed at baseline, 1 month, and 2 months. For other outcomes, including adverse drug reactions (ADRs), there were no significant differences between the groups. Conclusions: The combination of propranolol (40 mg) and flunarizine (10 mg) demonstrated superior efficacy over amitriptyline (10 mg) after prolonged treatment, while its effectiveness was comparable to other groups at earlier time points. ADRs were similar across all groups.